PENGARUH MEDIA SOSIAL TERHADAP KEPUTUSAN MEMILIH STUDI MAHASISWA DENGAN BRAND AWARENESS SEBAGAI VARIABEL MEDIASI DI POLITEKNIK LP3I JAKARTA KAMPUS JAKARTA UTARA - Edih Abdulah; Mulyadi Suhardi (JURNAL LENTERA BISNIS, 2026)
The increasing competition between private and public higher education institutions requires LP3I Polytechnic Jakarta, North Jakarta Campus, to strengthen its brand awareness through social media. However, the high level of information exposure on social media does not necessarily encourage prospective students to make study selection decisions. This study aims to analyze the effect of social media on students’ study selection decisions with brand awareness as a mediating variable at LP3I Polytechnic Jakarta, North Jakarta Campus. This study employed a quantitative approach involving 120 students selected using proportional sampling based on the Slovin formula. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that social media has no significant effect on brand awareness (coefficient = -0.141; p = 0.189) or on study selection decisions (coefficient = 0.168; p = 0.127). In contrast, brand awareness has a positive and significant effect on study selection decisions (coefficient = 0.280; p = 0.007). The mediation analysis reveals that brand awareness does not mediate the effect of social media on study selection decisions because the relationship between social media and brand awareness is not statistically significant. These findings suggest that social media has not yet become a primary factor influencing students’ study selection decisions, whereas brand awareness plays a significant role in encouraging such decisions. Keywords: Social Media, Brand Awareness, Study Selection Decision, Private Higher Education Institution.